Bayesian Inference of Noise Levels in Regression - Bishop, Christopher; Qazaz, C. S. (Proceedings 1996 International Conference on Artificial Neural Networks, ICANN'96, Bochum, Germany, 1997)
In most treatments of the regression problem it is assumed that the distribution of target data can be described by a deterministic function of the inputs, together with additive Gaussian noise having constant variance. The use of maximum likelihood to train such models then corresponds to the minimization of a sum-of-squares error function. In many applications a more realistic model would allow the noise variance itself to depend on the input variables. However, the use of maximum likelihood for training such models would give highly biased results. In this paper we show how a Bayesian treatment can allow for an input-dependent variance while overcoming the bias of maximum likelihood.